O conceito de natureza em Merleau-Ponty - Araújo, Vitor Vasconcelos de (2016)
This dissertation aims to describe the concept of Nature in the work of Merleau-Ponty, showing how the process of naturalization of phenomenology was essential in building a theory of Being. We want to show, above all, how is it possible, from such presentation, a sense of Nature that is not understood as the antithesis of consciousness, recognizing the first as the condition of the latter. This consideration leads us directly to the effort to recognize the Nature in its temporal and symbolic dimension, which in early works of the French philosopher remained as subsumed to the structures of human perception, or as the product of sensitive correlations of the body. First, we will show the constitution of Natural Being from two approaches, namely an epistemological, in Merleau-Ponty´s first works, in which the dialogue with the transcendental philosophies represented the very impossibility of a pure psychology, and an ontological approach, in which the inevitable development of a theory of natural Being is understood as a propaedeutic to the studies of the perception and the body. This path directly leads us, finally, to identify in the course Nature an ontological scale of natural Being, recognizing in it the position of a primary Being.